DABCO-Catalyzed Synthesis of Thiazolidine-2-thiones: System Development and Mechanistic Insights - Chalkidis, Savvas G.; Hong, Sungil; Tsiadi, Anthi Markella; Fika, Evangelia; Tsoureas, Nikolaos; Mpourmpakis, Giannis; Georgios C. Vougioukalakis (Journal of Organic Chemistry, 2025)
A base-catalyzed protocol is reported for the construction of 1,3-thiazolidine-2-thione scaffolds bearing quaternary carbon centers from carbon disulfide and α-tertiary propargylamines. The reaction proceeds using low catalyst loading, under ambient temperatures, and in the absence of solvent. Various α-tertiary propargylamines have been employed, affording a series of previously unreported thiazolidine-2-thione compounds and avoiding purification via column chromatography in certain cases. We also describe a one-pot strategy for the synthesis of the same products through a KA2 coupling-CS2 incorporation approach. The reaction mechanism and substituent-dependent catalytic behavior were studied through a combination of detailed experimental and computational studies.